THE STUDY OF BIM ON MINIMIZING THE VIOLATION OF SAFETY RULES IN INFRASTRUCTURE PROJECT - Mohsin, Arissa Azreen (Universiti Teknologi PETRONAS, 2021)
Since the construction industry has been listed as the highest number of deaths and injury rates among all sectors of the industry, there are many studies that show all these safety incidents can be prevented by safety preparation using Building Information Modelling (BIM) at design and development stages. The number of deaths and injuries could be minimized by understanding and applying safety concern at the preconstruction level. Since safety concerns are a major concern in the construction industry, a lot of safety measures have been taken on construction sites, but only a few of them have been introduced in construction, most of which are only to avoid being punished by the law. Therefore, the aim of this study is to study the importance of BIM on minimizing the violation of safety rules in infrastructure project.